Scientific collaboration: genuine and false motivators - Volpato, Gilson Luiz [UNESP] (My University, 2013)
Here, I emphasize the need for collaborative research among scientists. Such collaboration should aim to address the genuine integrative need to build knowledge rather than searching for visibility based on the international prestige of a collaborator, increased productivity, or funding. Scientists must provide a valid and honest counterpart, such as a solid scientific proposal and performance, and avoid opportunistic motivators.
Keywords: Science; Cooperation; Research funding